Hubungan Perilaku Bullying dengan Kesehatan Mental Siswa Kelas VII SMPN 3 Limboto Barat Kabupaten Gorontalo - Nur Uyuun I Biahimo; Firmawati; Egi Fatma Tuliabu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: to identify the impact caused by bullying is very wide in scope, including depression, anxiety and sleep problems that may carry over into adulthood, physical health complaints, such as headaches, abdominal pain and muscle tension, insecurity when in the school environment and decreased enthusiasm for learning and academic achievement Methods: This article quantitative research design with a descriptive-correlation approach. The object of the study were all grade VII students at SMP Negeri 3 Limboto with totali 57 respondent using a total sampling technique. The research instrument uses Olweus Bully/Victim Questionnaire (OBVQ) and Mental Health Inventory (MHI). The data were analyzed with Chi-square. Results: The results showed that students who experienced high bullying behavior with a high level of malaise were good at 21 people and poor as many as 9 people. Students who experienced bullying behaviors were good at 4 people and not good as many as 4 people. In addition, students who experienced bullying behaviors were good at least 16 people and not good as many as 3 people. Known statistical value or pValuel = 0.003 (<α 0.05). Conclusion: There is a relationship of Bullying Behavior with Student Behavior at SMPN 3 West Limboto.